Genetic variations and haplotypes in the annexin A5 gene are associated with the risk of recurrent pregnancy loss. Issue 10 (18th March 2019) - Lan, Yanli; Wang, Jing; Zhang, Qinghua; Yang, Xuezhou; Li, Lin; Yin, Jiu; Li, Hemei; Song, Xuan; Chen, Zhilan; Liu, Yun
Abstract: The expression of annexin A5 (ANXA5) was shown to affect the pathogenesis of recurrent pregnancy loss (RPL). In this study, the effects of two haplotypes, M1 and M2, on the transcription efficiency of ANXA5 promoter were explored. Correlation analysis was used to investigate the association between the single‐nucleotide polymorphism haplotypes in ANXA5 promoter and the risk of RPL. And a luciferase reporter assay was carried out to study the effects of haplotypes M1 and M2 on the transcription efficiency of the ANXA5 promoter. To study the association between ANXA5 haplotypes and the risk of RPL, real‐time polymerase chain reaction, western blot analysis, and immunohistochemistry assays were conducted to observe the expressions of ANXA5 messenger RNA (mRNA) and protein. Compared to M1 haplotype carriers, M2 haplotype carriers were associated with a higher risk of RPL. Additionally, compared to GATGTC haplotype carriers, GATGGC haplotype carriers were associated with a higher risk of RPL. Compared with RPL cases, the incidences of M2 haplotype were lower in both the population control and parous control cases. Furthermore, M2 carriers showed more significantly decreased activity of ANXA5 promoter compared to the carriers of other haplotypes, indicating that the haplotypes of ANXA5 promoter may be used as a potential biomarker to predict the prognosis of RPL. Moreover, the activity of ANXA5 as well as the mRNA/protein expression of ANXA5 was significantly downregulated in RPL patients, indicating that the M2 haplotype significantly increased the risk of RPL. Therefore, haplotype M2 increased the risk of RPL by inhibiting the expression of ANXA5. Abstract : In this study, we suggested that the M1/M2 haplotypes in the ANXA5 gene were associated with an increased risk of RPL. We showed that the expression of ANXA5 was decreased in the carriers of the M2 haplotype. Therefore, the presence of the M2 haplotype in ANXA5 might be used as a novel biomarker to predict the prognosis of RPL.